2021
DOI: 10.1002/cti2.1321
|View full text |Cite
|
Sign up to set email alerts
|

miR‐21 sustains CD28 signalling and low‐affinity T‐cell responses at the expense of self‐tolerance

Abstract: Objective miR‐21 is highly expressed in iNKT and activated T cells, but its T‐cell autonomous functions are poorly defined. We sought to investigate the role of miR‐21 in the development and functions of T and iNKT cells, representing adaptive and innate‐like populations, respectively. Methods We studied mice with a conditional deletion of miR‐21 in all mature T lymphocytes. Results Thymic and peripheral T and iNKT compartments were normal in miR‐21 KO mice. Upon activation in vitro, miR‐21 depletion reduced T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 68 publications
(175 reference statements)
2
1
0
1
Order By: Relevance
“…A recent study supports our findings and defines the role of miR-21 in acting as a critical rheostat facilitating the T-and iNKT-cell response towards low-affinity antigens (Fedeli et al, 2021). Especially for iNKT cells, miR-21 is the most highly upregulated miRNA compared to conventional T cells (Fedeli et al, 2009).…”
Section: Mir-21: Dynamically Expressed In the Thymus But Largely Redu...supporting
confidence: 87%
See 3 more Smart Citations
“…A recent study supports our findings and defines the role of miR-21 in acting as a critical rheostat facilitating the T-and iNKT-cell response towards low-affinity antigens (Fedeli et al, 2021). Especially for iNKT cells, miR-21 is the most highly upregulated miRNA compared to conventional T cells (Fedeli et al, 2009).…”
Section: Mir-21: Dynamically Expressed In the Thymus But Largely Redu...supporting
confidence: 87%
“…Surprisingly, absence of miR-21 does not result in altered frequencies of iNKT cells as shown by us and others (Kunze-Schumacher et al, 2018;Fedeli et al, 2021) (Figure 38). In the recent study by Fedeli et al (2021), miR-21 was identified to sustain CD28-dependent costimulation pathways and KO mice showed enhanced resistance towards experimental autoimmune encephalomyelitis. These experiments support our findings of miR-21 rather acting in fine-tuning T-cell responses than controlling a particular step of T-cell development.…”
Section: Mir-21: Dynamically Expressed In the Thymus But Largely Redu...supporting
confidence: 50%
See 2 more Smart Citations